2010
DOI: 10.1007/s00253-010-2575-6
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization of PCBs by the genetically modified strain Cupriavidus necator JMS34 and its application for bioremediation of PCBs in soil

Abstract: Polychlorobiphenyls (PCBs) are classified as "high-priority pollutants." Diverse microorganisms are able to degrade PCBs. However, bacterial degradation of PCBs is generally incomplete, leading to the accumulation of chlorobenzoates (CBAs) as dead-end metabolites. To obtain a microorganism able to mineralize PCB congeners, the bph locus of Burkholderia xenovorans LB400, which encodes one of the most effective PCB degradation pathways, was incorporated into the genome of the CBA-degrading bacterium Cupriavidus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 57 publications
1
20
0
2
Order By: Relevance
“…Central pathways involve the fission by a dioxygenase of the dihydroxylated aromatic metabolic intermediates at ortho - or meta -position and lead to the formation of Krebs cycle intermediates [1][4]. Bacterial metabolism of aromatic compounds has been extensively studied [3][11]. The metabolic reconstruction of aromatic compounds pathways in in model environmental bacteria has been achieved by genome sequence analyses [3], [12][14].…”
Section: Introductionmentioning
confidence: 99%
“…Central pathways involve the fission by a dioxygenase of the dihydroxylated aromatic metabolic intermediates at ortho - or meta -position and lead to the formation of Krebs cycle intermediates [1][4]. Bacterial metabolism of aromatic compounds has been extensively studied [3][11]. The metabolic reconstruction of aromatic compounds pathways in in model environmental bacteria has been achieved by genome sequence analyses [3], [12][14].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, strain MSR33 showed a high mercury volatilization rate, 6 . Strain MSR33 was able to cleave the organic moiety from methylmercury and to reduce Hg 2+ into a less toxic Hg elemental form.…”
Section: Discussionmentioning
confidence: 98%
“…Bioremediation is an attractive technology for the clean-up of polluted waters and soils [1][2][3][4][5][6]. Mercury is one of the most toxic elements in the environment [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Many of the other groups enriched under the preincubation conditions have been associated with hydrocarbon degradation, but not necessarily PAH degradation ( Jeon et al, 2004;Kasai et al, 2006;Popp et al, 2006;Han et al, 2009;Saavedra et al, 2010).…”
Section: Figmentioning
confidence: 99%